White writers and Shaka Zulu - Wylie, Dan (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1996)
The figure of Shaka (c. 1780-1828) looms massively in the historical and symbolic landscapes of Southern Africa. He has been unquestioningly credited, in varying degrees, with creating the Zulu nation, murderous bloodlust, and military genius, so launching waves of violence across the subcontinent (the "mfecane"). The empirical evidence for this is slight and controversial. More importantly, however, Shaka has attained a mythical reputation on which not only Zulu self-conceptions, but to a significant degree white settler self-identifications have been built. This study describes as comprehensively as possible the genealogy of white Shakan literature, including eyewitness accounts, histories, fictions and poetry. The study argues that the vast majority of these works are characterised by a high degree of incestuous borrowing from one another, and by processes of mythologising catering primarily to the social-psychological needs of the writers. So coherent is this genealogy that the formation of an idealised notion of settler identity can be discerned, especially through the common use of particular textual "gestures". At the same time, while conforming largely to unquestioning modes of discourse such as popularised history and romance fiction, individual writers have attempted to adjust to socio-political circumstances; this study includes four close studies of individual texts. Such close stylistic attention serves to underline the textually-constructed nature of both the figure of Shaka and the "selves" of the writers. The study makes no attempt to reduce its explorations to a single Grand Unified Explanation, and takes eclectic theoretical positions, but it does seek throughout to explore the social-psychological meanings of textual productions of Shaka - in short, to explore the question, Why have white writers written about Shaka in these particular ways?
Keywords: Shaka, Zulu Chief, 1787?-1828 In literature; Shaka, Zulu Chief, 1787?-1828; Zulu (African people) -- History